An efficient way of third-order dispersion compensation for reshaping parabolic pulses through normal dispersion fiber amplifier. (21st August 2018) - Chowdhury, Debasruti; Ghosh, Dipankar; Basu, Mousumi
Abstract: Normal dispersion decreasing fibers (NDDFs) employed for parabolic pulse (PP) generation are limited by the presence of inherent third-order dispersion (TOD), which leads to distortion in pulse shape from its parabolic nature. This necessitates a compensation method for TOD for such fibers. Dispersion-compensating fiber (DCF) amplifiers with relatively smaller values of dispersion can also be largely affected by this harmful effect of TOD when used for the same purpose. As a solution, a time-reversal system (TRS) based on a time-conjugating technique is employed with the aim of minimizing the deleterious effects of TOD. A detailed study on the estimation of the critical length where the time lens system needs to be implemented within the fiber link is crucial for reshaping the pulse into parabolic form. An NDDF is designed and optimized to possess a relatively higher value of TOD and a cascaded fiber optic system comprising the first stage of the proposed NDDF, the TRS and the second stage of the NDDF is suggested here to obtain linearly chirped PP at the output end even in the presence of a high value of TOD. The proposed scheme has also proved to be efficient for better pulse reshaping through DCFs possessing a high amount of TOD.